PENGARUH LIKUIDITAS DAN RISIKO SISTEMATIS TERHADAP RETURN SAHAM PADA PERUSAHAAN YANG TERDAFTAR DI BEI - Indah Aulia Rahmi (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2022)
This research aims to identify the effect of liquidity and systematic risk on stock returns in companies listed on the Indonesia Stock Exchange in 2015-2019. The population used is all companies listed on the Indonesia Stock Exchange from 2015 to 2019. The sampling method is carried out by using purposive sampling method with a sample of 134 companies. The analytical method used is panel data regression analysis with the help of the E Views 8 application. The independent variables used in this research are liquidity and systematic risk, while the dependent variable is stock returns. The research results show that liquidity has no significant effect on stock returns, while systematic risk has a positive and significant effect on stock returns